(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The theory of relativity has been at the pinnacle of human scientific thought for 120 years. However, whether it should continue to lead is a question for us. Voices questioning the theory of relativity have been continuing, but since they are mostly from a mathematical or experimental point of view, they have not yielded convincing results. We have pioneered a new way of analyzing mathematical models from the perspective of reviewing the rationality of physical models, thus we have seen many problems with relativistic models from different perspectives, which we have grouped into three general concerns and 12 obvious or easy to prove problems. Through these intuitive discussions, we believe that the theory of relativity should no longer lead the scientific and technological thinking of mankind. This article focuses on special relativity. We will continue to discuss general relativity in future articles.